Upaya Guru PAI dalam Pembentukan Akhlaqul Karimah di Sekolah Dasar - Nuraini Nuraini; Rahmi Wiza (Jurnal Kawakib, 2021)
This study aims to determine the morals of students at the UNP Laboratory Development Elementary School, to find out the efforts of Religion teachers in providing examples, guidance, historical stories, encouragement, and fostering students' conscience and to know the supporting and inhibiting factors for teachers in shaping students' morality. This type of research is qualitative with descriptive method, because the research describes, tells, and interprets a situation or event as it is. The results of this study were that students still spoke in high-pitched voices, running around in front of the office, and their hair was still long. Efforts made by Religion teachers are a) Providing an example with Tahfiz, b) Encouraging performing Dzuhur prayers in congregation, c) Equipping common sense with knowledge through historical stories, d) Advising parents to get along with good people, e) Encouraging to leave the nature of lazy. The driving factors in the formation of akhlaq karimah are parents, student motivation, and the community. Meanwhile, the inhibiting factors in the formation of akhlaqul karimah are socio-economic conditions and education level.